Peningkatan Literasi Keuangan Siswa Kelas V Sekolah Dasar melalui Edukasi Pengelolaan Uang Saku, Menabung, dan Belanja Bijak - Tommy Kuncara; Windy Dwiparaswati; Abednego Priyatama; Fera Riske Anggita; Sandy Suryady (Asosiasi Dosen Muda Indonesia, 2026)
Financial literacy is a fundamental skill that should be introduced to children from elementary school age. An understanding of the value of money, pocket-money management, saving habits, and the ability to distinguish needs from wants can help students make more responsible financial decisions. This community service program aimed to improve the financial literacy of fifth-grade elementary school students through education on pocket-money management, saving, and wise spending. The program was conducted at SDN Margahayu XIII, Bekasi City, on June 15, 2026, involving 30 fifth-grade students. An educational and participatory approach was applied through interactive presentations, needs-and-wants games, pocket-money allocation simulations, saving-goal preparation, simple financial-recording exercises, and wise-shopping simulations. The program was evaluated using pre-tests, post-tests, student worksheets, and participant-observation sheets. The results showed that the students’ average financial literacy score increased from 53.8 in the pre-test to 85.0 in the post-test. The score increased by 31.2 points or 58.0%. A total of 27 students, or 90.0%, achieved a minimum post-test score of 75, while 29 students, or 96.7%, demonstrated improved scores. The highest improvement was found in the students’ ability to distinguish needs from wants, which increased by 33 points. These results demonstrate that contextual learning through games and simulations can improve students’ understanding of pocket-money management, saving, and responsible shopping decisions. This program is expected to become an initial step in developing economical, planned, disciplined, and responsible financial behavior among elementary school students.